Production of Botanical Seeds and Shallot Boobs with Vernalization and Giberrylin (GA3) Treatment in Highland Areas - Abubakar Idhan; Elkawakib Syam’un; Muh. Riyadi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Vernalization and Gibberellin (GA3) solution can be applied to simultaneously increased shallot production and TSS (True Shallot Seed) in the highlands. The research aimed to obtain shallot varieties that are able to naturally flower more and have high growth and production. This research was carried out in the form of split plot experimental design. The main plots consisted of five shallot varieties selected from the adaptation test, which resulted from planting in the lowlands and highlands, namely the Bima Brebes variety (V1), Manjung variety (V2), Bauji variety (V3), Bangkok Jeneponto variety (V4), Mentes variety (V5). The sub-plots consisted of 4 stratifications of vernalization temperature, namely: room temperature (F1), 4°C (F2), 8°C (F3) and 12°C (F4). The sub-sub-plots consist ed of 4 concentrations of gibberellins GA3 in aquades, namely: 0 ppm (H1), 50 ppm (H2), 75 ppm (H3), and 100 ppm (H4). Each treatment was repeated three times, so as to obtain as many as: 5 x 4 x 4 x 3 = 240 experimental plots. Results showed that shallot varieties have different responses to vernalization and gibberellin GA3 treatment. No stratum of vernalization temperature and certain GA3 concentrations were found that consistently supported certain observational parameters on the growth and production of five shallot varieties. Manjung and Bauji varieties were observed as having great potential to produce more flowers and botanical seeds in highlands. Keywords: Giberrylin, Highlands, Shallot boob, TSS, Vernalization.